Rural Marketing - Dr. Pratima (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
Rural markets offer a great scope for a concentrated marketing effort because of the recent increase in the rural incomes. Such incomes will increase faster because of better production and higher prices for agricultural commodities. Rural marketing is a process of developing, pricing, promoting, and distributing rural specific goods and services leading to desired organizational objectives exchange with rural customers to satisfy their needs and wants, and also to achieve. Rural marketing is a developing concept, and the marketers have realized the opportunity of growth in the market recently. Any macro level strategy for these markets should focus on availability, accessibility and affordability. Focused attention needs to be paid to market research, key decision areas, problems and rural marketing environment, to reduce the uncertainly in dealing with these markets. This paper discusses the rural marketing and its strategies and also focuses on issues and challenges, problems, key decision areas and rural marketing environment.